Role of pharmaceutical care for self‐administered pulmonary tuberculosis treatment in Thailand. (19th March 2017) - Tanvejsilp, P.; Pullenayegum, E.; Loeb, M.; Dushoff, J.; Xie, F.
Summary: What is known and objective: With resource constraints in Thailand, directly observed therapy (DOT) for treating tuberculosis (TB) may not be feasible to implement. To improve patients' adherence, hospitals either modify DOT or adopt different approaches: pharmaceutical care or home visit. Our objective was to assess pulmonary TB treatment success rate of pharmaceutical care compared to home visit and modified DOT in Thailand. Methods: We conducted a retrospective cohort study using data collected in adult pulmonary TB patients starting treatment between October 2010 and September 2013 in three hospitals in Thailand. This study was approved by the Research Ethics Board at each of the participating hospitals. We built a propensity score matching to account for differences in patient baseline characteristics. Results: Analysis included 1398 patients. Before matching, the treatment success rate for patients receiving pharmaceutical care was 94.9%, home visit 93.6% and modified DOT 90.1%. The propensity score‐matched cohorts indicated that differences in the treatment success rate were not statistically significant when comparing pharmaceutical care with either home visit (success rate: 92.76% vs 94.74%, risk difference: 1.97%, 95% CI −3.64 to 7.59) or modified DOT (success rate 93.37% for both, risk difference: 0%, 95% CI −5.30 to 5.30). What is new and conclusion: Pharmaceutical care, home visit and modified DOT are all associated with high success rate for pulmonary TB treatment and exceeded the WHO target, in this retrospective analysis. Abstract : We conducted a retrospective cohort study in Thailand, where directly observed therapy (DOT), a WHO recommended strategy for treating tuberculosis, is not feasible to widely implement. Pharmaceutical care is one of several approaches that was adopted for enhancing TB treatment adherence. However, data demonstrating the effectiveness of pharmaceutical care in TB treatment is limited. We found that pharmaceutical care was shown to have similar effectiveness in achieving TB treatment success compared with home visit and the modified DOT. All three TB treatment strategies exceeded the WHO target.